Rapid Lithium Diffusion in Order@Disorder Pathways for Fast‐Charging Graphite Anodes. Issue 1 (23rd October 2020) - Cai, Wenlong; Yan, Chong; Yao, Yu-Xing; Xu, Lei; Xu, Rui; Jiang, Li-Li; Huang, Jia-Qi; Zhang, Qiang
Abstract : Fast‐Charging Batteries In article number 2000010, Qiang Zhang and co‐workers show that the coating layer on graphite anode affords abundant active sites and fast diffusion pathways to accelerate the transportation of Li ions. The improved Li ion diffusion renders superior rate performance. This fresh understanding holds great potential for facilitating the practical applications of graphite in fast‐charging batteries.